Differences in Parental Participation in the Maintenance of Children's Dental Health between Carious and Non-Carious: Perbedaan Partisipasi Orang Tua dalam Pemeliharaan Kesehatan Gigi Anak antara yang Karies dan Tidak Karies - Ayu Permata Sari; Budi Suryana; Damhuji Damhuji (Poltekkes Kemenkes Kupang, 2020)
Oral and dental health is a very important concern in health development, one of which is caused by the vulnerability of the school-age group of children from dental health problems. School age is a time to lay a solid foundation for the realization of quality human beings and health is an important factor in determining the quality of human resources. The purpose of this study was to determine the participation of parents in the maintenance of dental health between carious and non-carious children at SDN 40 North Pontianak. This type of research is a case control study, an analytical survey research that concerns how risk factors are studied. The population in this study were all parents of students, grade 1 SDN 40 North Pontianak aged 7 and 8 years who were carious and not carious as many as 78 people. This study used a sample of 60 people divided into 2, namely 30 samples for children with caries and 30 samples for children without caries. The results of this study were obtained from 60 respondents. The p value <0.05 means that there is a significant difference, namely the difference in parental participation between those with and without caries. Children without caries can be said that parental participation in maintaining children's dental health is better than children with caries. The conclusion of this study was that there was a significant difference between parental participation in the maintenance of children's dental health between those with and without caries. Kesehatan gigi dan mulut menjadi perhatian yang sangat penting dalam pembangunan kesehatan yang salah satunya disebabkan oleh rentannya kelompok anak usia sekolah dari gangguan kesehatan gigi. Usia sekolah merupakan masa untuk meletakkan landasan kokoh bagi terwujudnya manusia yang berkualitas dan kesehatan merupakan faktor penting menentukan kualitas sumber daya manusia. Tujuan penelitian ini adalah untuk mengetahui partisipasi orang tua dalam pemeliharaan kesehatan gigi anak antara yang karies dan tidak karies pada SDN 40 Pontianak Utara. Jenis penelitian ini adalah penelitian case control suatu penelitian survey analitik yang menyangkut bagaimana faktor risiko yang dipelajari. Populasi dalam penelitian ini adalah seluruh orang tua siswa, kelas 1 SDN 40 Pontianak Utara yang berusia 7 dan 8 tahun yang karies dan tidak karies sebanyak 78 orang. Penelitian ini menggunakan sampel sebanyak 60 orang dibagi menjadi 2 yaitu 30 sampel untuk anak dengan karies dan 30 sampel anak tanpa karies. Hasil dari penelitian ini didapat dari 60 responden. Didapatkan nilai p<0,05 yang berarti bahwa terdapat perbedaan yang signifikan yaitu perbedaan partisipasi orang tua antara yang karies dan tanpa karies. Anak tanpa karies dapat dikatakan partisipasi orang tua dalam memelihara kesehatan gigi anak, lebih baik dibandingkan anak dengan karies. Kesimpulan dari penelitian ini didapatkan bahwa terdapat perbedaan yang signifikan antara partisipasi orang tua terhadap pemeliharaan kesehatan gigi anak antara yang karies dan tanpa karies.